Rola gospodarki cyrkulacyjnej w rozwoju miast (The Role of a Circular Economy in the Urban Development) - Piłat-Borcuch, Magdalena (The journal of contemporary issues in business and government, 2021)
The purpose of the article is to present the problems of the circular economy in an urban context. An economy whose system is based on raw materials obtained from waste, which allows not only to reduce costs related to the functioning of cities, but to improve the quality of life in cities. The article presents the change in the logic of the functioning of cities, highlighting their ecological face. The assumptions of the circular economy were presented, emphasizing the necessity and irreversibility of implementing its assumptions. Then, reference was made to Chinese and European examples of the implementation of the circular economy assumptions.